Cooling, exhumation, and deformation in the Hindu Kush, NW Pakistan: New constraints from preliminary 40Ar/39Ar and fission track analyses. (1st June 2018) - Faisal, Shah; Larson, Kyle P.; Camacho, Alfredo; Coutand, Isabelle
Graphical abstract: Highlights: New thermochronologic data are presented from north Pakistan. 40 Ar/ 39 Ar data record the reactivation of structures during initial Himalayan collision. Extreme topography in northern Pakistan may be related to Pleistocene exhumation. Abstract: Asian crust in the Hindu Kush region in northern Pakistan records a protracted history of rifting, subduction and collision not commonly preserved within the Himalaya. Because of this, it is key to understanding the development of the southern Eurasian margin both prior to and after collision with India. New mica 40 Ar/ 39 Ar and apatite fission track geochronologic data from this region provide constraints on the kinematics of the Hindu Kush. 40 Ar/ 39 Ar muscovite and biotite ages from the late Cambrian Kafiristan pluton are 379.7 ± 1.7 Ma and 47.2 ± 0.3 Ma, respectively. The muscovite age may record cooling or partial resetting, while the biotite age is interpreted to record a thermal disruption associated with the early stages of continental collision in the Himalayan system. A 111.0 ± 0.6 Ma muscovite age from the northern part of the Tirich Mir pluton (∼123 Ma old; U-Pb) is interpreted to indicate a recrystallization event ∼12 Myrs after its intrusion. In addition, a younger muscovite age of 47.5 ± 0.2 Ma was derived from the opposite side of the same pluton in the immediate hanging wall of the Tirich Mir fault. This Eocene age is interpreted to represent the time of recrystallization during fault (re)activation in the early stages of India-Asia continent-continent collision. 40 Ar/ 39 Ar biotite analysis from the Buni-Zom pluton yields an age of 61.6 ± 1.1 Ma and is interpreted to reflect cooling at mid-upper crustal levels subsequent to the pluton's emplacement in the middle Cretaceous. Finally, 17.1–21.3 Ma 40 Ar/ 39 Ar ages from the Garam Chasma pluton and surrounding metapelites indicate cooling immediately following crystallization of the leucogranite body in the earliest Miocene/latest Oligocene. The younger cooling history is resolved by fission track dating of apatite (AFT). In the vicinity of the bounding Tirich Mir fault, the Tirich Mir pluton yields an AFT age of 1.4 ± 0.3 Ma, which is consistent with active exhumation associated with the surface uplift of the 7700+ m Tirich Mir peak. The Garam Chasma pluton has a young age of 3.5 ± 0.2 Ma, which also records rapid rock uplift and exhumation in the area. Finally, an AFT age of 9.1 ± 2.1 Ma was extracted from a metapelite in the footwall of an east verging thrust fault separating it from the Garam Chasma pluton to the west. The difference in ages, Pliocene vs. late Miocene, reflect differential cooling/exhumation paths across that structure.